2020
DOI: 10.3390/met10081083
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Microwave Reductive Roasting Process of Bauxite Residue

Abstract: In this study, microwave-assisted heating is presented as a suitable method to transform the hematite and goethite contained in bauxite residue into magnetite, wüstite, and metallic iron, with a short processing time. The final target was the production of a sinter with strong magnetic properties, allowing the magnetic separation of Fe from the residue. The influence of microwave energy on the sample, the effect of irradiation time, and the carbon/bauxite residue mass ratio (C/BR) were the parameters that have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The numerical model integrated the estimated electromagnetic power density over the entire specimen domain to determine the microwave power absorbed. Similar studies were reported in References 61, 65–67. As explained earlier, the material's dielectric properties control how much microwave power is absorbed 67 .…”
Section: Resultssupporting
confidence: 75%
“…The numerical model integrated the estimated electromagnetic power density over the entire specimen domain to determine the microwave power absorbed. Similar studies were reported in References 61, 65–67. As explained earlier, the material's dielectric properties control how much microwave power is absorbed 67 .…”
Section: Resultssupporting
confidence: 75%
“…Simultaneously, extraction technology is more effective in leaching such as chemical technology for the separation of various minerals. The leaching of red mud or sintered red mud is very effective in various sectors for the adsorbents and catalyst categories [ 78 , 79 , 80 ]. The red mud–fly ash mixtures could be considered as a sustainable acid mine drainage management system.…”
Section: Fields Of Application Of Red Mudmentioning
confidence: 99%
“…The composition of bauxite residue varies depending on the source of the bauxite ore and the specific processing methods employed. Generally, bauxite residue consists of several major components, with the most significant ones being metallic oxides and hydroxides like iron, titanium, aluminum, silicon, calcium, and sodium [4]. These compounds, in particular, play a crucial role in determining the properties and potential environmental impacts of the bauxite residue.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium is one of the most significant impurities found in bauxite residue, although its presence can vary depending on the source of the bauxite ore and the processing methods used. Titanium is commonly present in bauxite residue in the form of titanium oxides, such as rutile and anatase (TiO 2 ), cancrinite (CaTiO 3 ), and ilmenite (FeTiO 3 ) [4]. For the recovery of Ti from BR, numerous studies have been carried out, primarily by looking at hydrometallurgical processes [5][6][7].…”
Section: Introductionmentioning
confidence: 99%